Хлеб да соль! Добро пожаловать в Удмуртию! - Волкова Н. А. (Регион - Пресс, 2008)
Экземпляры: (20130424) / Инвентарный номер: 48389 / Цена: 300.00 / Сис.шифр: 92 48389 / Авт.знак: Х 55 / ГРНТИ: 65.13 / ББК: 92